FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN RUMAH TAPAK SEDERHANA DI PARUNG PANJANG - Charlescian Anggi; Nurahma Tresani; Liong Ju Tjung (Universitas Tarumanagara, 2022)
The high demand for housing caused by the increasing number of urban residents and the limited land to be used as residential areas is one of the reasons residential property prices in cities have soared. The need for housing is increasing but there is no provision in the city center, so that demand is being met outside Jakarta, such as in the areas around Bogor, Depok, Tangerang and Bekasi. The Parung Panjang area, Bogor is one area that is being eyed by many private developers in the development of affordable, simple-sided houses. Affordable land prices coupled with factor support from public transportation services in the form of mass electric rail train (KRL) transportation have made the development of simple housing on a site in Parung Panjang successfully absorbed by the market. The high interest from the public to own simple landed houses in the Parung Panjang area has made residential property developers flock to offer their respective property products to the general public. In their journey, these residential property developers certainly do not experience smooth sailing due to the rivalry factor from other property developers, therefore every property developer is required to innovate in developing simple tread housing that is not only affordable, but also able to fulfill the following aspects: aspects desired by potential customers. So this research is directed to examine the factors that influence consumers in making purchasing decisions and the relationship between consumer characteristics and the relationship between consumer characteristics and purchasing decisions for simple landed houses in Parung Panjang, Bogor. This research is a descriptive quantitative research and the distribution of questionnaire surveys was carried out to respondents who had been previously selected, namely residents of the Sentraland Paradise and The River housing estates. The results of the research from 30 respondents showed that economic and environmental factors were the main factors in buying housing in Parung Panjang because almost all consumers in the housing said this was very important. Keywords: House, purchase decision, property, developer Abstrak Tingginya permintaan hunian yang disebabkan oleh meningkatnya jumlah penduduk perkotaan dan terbatasnya lahan yang akan digunakan sebagai area perumahan adalah salah satu alasan harga properti residensial di kota melambung tinggi. Kebutuhan akan hunian meningkat tetapi penyediaan di pusat kota tidak ada, sehingga kebutuhan tersebut terpenuhi di luar Jakarta, seperti dikawasan sekitar Bogor, Depok, Tangerang dan Bekasi. Daerah Parung Panjang, Bogor adalah salah satu kawasan yang sedang banyak dilirik oleh pengembang swasta dalam pengembangan rumah sederhan tapak yang terjangkau. Harga tanah yang terjangkau ditambah dukungan faktor dari layanan transportasi umum berupa transportasi masal kereta rel listrik (KRL) membuat pengembangan perumahan sederhana tapak di Parung Panjang berhasil terserap oleh pasar. Minat yang tinggi dari masyarakat untuk memiliki hunian rumah sederhana tapak di daerah Parung Panjang membuat para pengembang properti perumahan berbondong-bondong untuk menawarkan produk properti masing-masing kepada khalayak umum. Dalam perjalanannya, para pengembang properti perumahan ini tentu tidak serta merta mengalami jalan yang lancar dikarenakan faktor rivalitas dari para pengembang properti lain, oleh karena itu setiap pengembang properti diwajibkan untuk berinovasi dalam mengembangkan perumahan tapak sederhana yang tidak hanya terjangkau, namun juga dapat memenuhi aspek-aspek yang diinginkan para calon konsumennya. Maka penelitian ini diarahkan untuk meneliti faktor–faktor yang mempengaruhi konsumen dalam pengambilan keputusan pembelian dan hubungan karakteristik konsumen terhadap pengambilan keputusan pembelian hunian rumah tapak sederhana di Parung Panjang, Bogor. penelitian ini adalah penelitian kuantitatif deskriptif dan penyebaran survei kuesioner dilakukan pada responden yang telah dipilih sebelumnya, yaitu penghuni perumahan Sentraland Paradise dan The River. Hasil penelitian dari 30 orang responden menunjukan bahwa Faktor ekonomi dan lingkungan merupakan faktor utama dalam pembelian perumahan di Parung Panjang karena hampir semua konsumen pada perumahan tersebut mengatakan hal tersebut sangat penting.